Teaching Vocabulary Using Snowball Throwing Technique - Yaqin, Muhammad Ainul; Sriwulandari, Novi; Dewi, Risma Kartika; Ihsan, Mas Darul; Trisnantasari, Ika; Ndaung, Ernita (Community: Jurnal Pengabdian Kepada Masyarakat, 2022)
This study aims to improve vocabulary mastery by using the snowball throwing technique on seventh-grade students at MTs. Mambaul Ulum Lamongan in the 2021/2022 academic year. Considering that many students find it difficult to master vocabulary, this study focuses on the use of the snowball throwing technique, which can help students improve their vocabulary mastery. The research design is Classroom Action Research (CAR). The research subjects are 21 seventh-grade students at MTs. Mambaul Ulum Lamongan during the 2018/2019 academic year. The results of this study indicate that in Cycle I, only 48% (10 students from the class) were able to achieve the success criteria, while 11 or approximately 52% of students did not meet the success criteria. Unlike Cycle I, the average score in Cycle II was quite satisfactory, with scores greater than or equal to 76, increasing to 76.19% (16 students in the class) who were able to meet the success criteria, and 5 or approximately 24% of students who did not meet the success criteria. Based on the results of student observations and post-tests, the improvement was quite significant. The application of the snowball throwing technique clearly helped students in achieving vocabulary. Finally, the author suggests that teachers apply the snowball throwing technique. Considering that the snowball throwing technique is a technique for solving problems in vocabulary mastery. By using various techniques in teaching English, especially in vocabulary mastery, students will enjoy learning more and automatically improve their vocabulary mastery.